Research Trends of Students’ Mathematical Ability on Algebra Materials Based on Gender: Bibliometric Analysis - Hayu, Sri Rah; Angraini, Lilis Marina (International Journal of Applied Learning and Research in Algebra, 2024)
Mathematical skills are not only used in the world of education but also in various professional fields, such as science, technology, and economics. This study uses blibliometric analysis whose data source is obtained from Google Scholar and uses the keyword of students' mathematical ability in algebra material based on gender with a maximum of 1000 data.   Researchers analyzed 948 out of 990 articles from 2019-2024. This study uses Publis or Perish software for data search through Google Scholar and VOSviewer to obtain analysis results that are by the objectives of this research was carried out to find out the research trends of mathematical abilities based on gender and to find out future research opportunities. This study shows that the most publications are in 2023 with 200 publications. The results of the research provide recommendations for variables that can be researched in the future, namely algebraic thinking and high mathematical ability.